Morphology, structure and electrochemical properties of single phase electrospun vanadium pentoxide nanofibers for lithium ion batteries - Cheah, Yan Ling (2011)
One-dimensional (1D) vanadium pentoxide (V2O5) nanofibers (VNF) are synthesized by electrospinning vanadium sol–gel precursors containing vanadyl acetylacetonate and poly(vinylpyrrolidone) followed by sintering. Crystal structure, molecular structure and morphology of electrospun VNF are analyzed using field emission scanning electron microscopy (FESEM), transmission electron microscopy (TEM), selected area diffraction (SAED), X-ray diffraction (XRD) and Fourier transform infrared spectroscopy (FT-IR). Single-phase electrospun VNF not, vert, similar300–800 nm in diameter, 20–50 μm long (aspect ratio > 50) with porous interconnected fibrous morphology are revealed by FESEM and TEM analysis. Electrochemical properties of the sintered VNF, as a cathode in lithium-ion batteries, explored using cyclic voltammetry (CV), galvanostatic charge/discharge and electrochemical impedance spectroscopy (EIS) give rise to new understandings of the electrochemical processes occurring in these nanofibrous cathodes. Electrospun VNF exhibits initial discharge capacity not, vert, similar316 mAh g−1 (not, vert, similar2.2 Li per V2O5) in the voltage range of 1.75 and 4.0 V vs. Li/Li+ at 0.1 C rate. When cycled at a reduced voltage range of 2.0–4.0 V vs. Li/Li+, less phase transitions occur, giving rise to the initial specific capacity of 308 mAh g−1 and improved cyclic retention of 74% after 50 cycles.